THE ROLE OF IMPLEMENTING OUT DOOR STUDYBASED LEARNING ON LEARNING OUTCOMES IN CLASS - Halek, Dahri Hi. (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The essence of teaching geography is to develop students' ability to recognize and understand natural phenomena and life about spatial and territoriality and to develop a positive rational attitude to deal with problems resulting from environmental influences. In this case, geography subjects at school must be based on the objectives of teaching geography, which will not be achieved if students only listen to lectures from the teacher in the classroom. Therefore, one of the appropriate forms of teaching and learning to achieve this goal is teaching and learning outside the classroom through outdoor study-based learning activities. The goal to be achieved from the role of implementing outdoor study learning is to generate interest and encouragement to discover what is learned. The research population is all students who carry out door study learning, namely 287 students. The sampling method is Proportional Random Sampling. The stages carry out the implementation of outdoor study learning in outdoor study learning, including preparation, implementation and follow-up. At the preparation stage, student participation in the committee was in the less category, namely 25%; student participation in determining tourist destinations was in the fewer criteria, namely 19.6% and preparing learning equipment in the good criteria, namely 96.4%. At the implementation stage, paying attention to field trip objects was in good criteria, namely, 98.2%. Listening and recording information was in good criteria. Namely, 91.1% and question and answer activities were in sufficient criteria, namely 67.9%. At the follow-up stage, making a report on the results of the field trip in the suitable criteria, namely 89.3%, and discussing the results of the field trip activities in the sufficient criteria, 64.3%. This proves that the stages of learning carry out outdoor study activities based on the outdoor study. Meanwhile, the contribution of the implementation of the Out Door Study to learning outcomes in geography subjects was 20.7%. This indicates an increase in student learning outcomes after implementing door study-based learning. Keywords: Role, Out Door Study, and Learning Outcomes